Studi Eksperimental Pengaruh Grid Turbulensi dan Fairing terhadap Karakteristik Aliran Terowongan Angin Menggunakan Tabung Pitot - Tunggal, Surjo Abadi Kencana (Jurnal FisTa Fisika dan Terapannya, 2026)
The investigation of airflow characteristics in wind tunnels is essential for various engineering applications, particularly in the aerospace field. This study aims to evaluate velocity distribution, boundary layer development, and the influence of turbulence using a Pitot tube as a simple and reliable instrument. The experimental method was conducted in a closed-circuit wind tunnel with measurements taken at several positions along the flow direction under conditions with and without a turbulence grid. The results show that the airflow velocity is not constant and tends to increase downstream due to boundary layer development. The presence of a turbulence grid increases the boundary layer thickness by approximately 2.5 times and induces velocity fluctuations, particularly near the inlet region. The installation of a fairing is shown to significantly reduce velocity deviation, from approximately 1 m/s to 0.5 m/s, thereby improving flow uniformity. It is concluded that the Pitot tube can be used to characterise the airflow. These findings imply that turbulence control and geometric modification of the wind tunnel are necessary to improve flow quality and the accuracy of aerodynamic measurements.